STUDY FENOMENA PENDIDIKAN KARAKTER PADA KLUB OLAHRAGA TAEKWONDO - Kusumawati, Dian (YLPK Mahardhika, 2024)
The increasing number of moral decline cases is a phenomenon that must be addressed immediately. The instillation of character values in the world of education is not only obtained through classroom education but also through continuity and sustainability outside the formal classroom, which plays a significant role in moral internalization. The continuous and sustainable application of character values becomes a solution to the many phenomena of moral degradation. The Taekwondo sports club is one of the means of instilling character education values that can be used as a tool in characterizing students. The purpose of the research is to understand how the phenomenon of character education is studied in taekwondo sports clubs and to identify the character values contained within these clubs. This research uses a descriptive quantitative approach. Five important elements in taekwondo are attitudes that must be possessed by taekwondo practitioners. Character values are formed through education at taekwondo sports clubs from the beginning to the end of training.